Corrigendum: Will the grass be greener on the other side of climate change? - Morris, Craig D.; Kirkman, Kevin P.; Zacharias, Pete J.K. (South African Journal of Science, 2023)
Original article: https://doi.org/10.17159/sajs.2022/13844 An error appears in the key (but not the data points) in Figure 3: the square symbol representing Sourveld should be depicted in orange, while the circle symbol representing Sweetveld should be depicted in green.